Application of edible coatings based on chitosan and cassava starch incorporated with tamarind seed extract in the preservation of guavas (Research, Society and Development, 2020)
Edible coatings incorporated with bioactive extracts have shown the potential to delay fruit ripening. The aim of this work was to evaluate the effect of edible coatings incorporated with tamarind seed extract (Tamarindus indica L.) on the physicochemical and microbiological characteristics of guavas during storage at room temperature for 10 days. Six coatings formulations were prepared and applied to guavas. The coated guavas demonstrated similar pH and firmness values and lower values of mass loss than those obtained with uncoated guavas on the tenth day of storage. Regarding color, similar values of L* and lower values of a* and b* were observed in relation to the control. In relation to microbial contamination, both coated and uncoated guavas showed aerobic mesophilic bacteria and mold and yeast counts between 102 and 103 CFU/mL on the tenth day of storage. The cassava starch and chitosan coatings incorporated with tamarind seed extract showed potential to be applied in the preservation of guavas stored at room temperature.